(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The goal of psychological research in personality is toestablish laws about, what difference will do in all kinds of social andgeneral environmental situations. Personality is concerned with all thebehaviour of the individual both over and under the skin. As the humancivilization developed with the long passage of time, human starts to collectthe knowledge, to transmit the accumulated knowledge to its younger generationand to enhance the present knowledge of field. This process is related keenlyto the development of human race. Gradually man’s society starts to establishvarious agencies and organisations for the all-round training of the youngergeneration. This process is called education which means the all-rounddevelopment of the personality.